Mechanism of water and nutrient competition between shelterbelts and farmland under different irrigation patterns in the Hexi Corridor oasis area, China - Yulian Hao; Haiyang Xi; Wenju Cheng; Tengfei Yu; Baofeng Li; Tuo Han; Yuqing Chen; Linbo Qu; Zhehui Wang (Soil and Tillage Research, 2026)

Dielectrically tuned core-shell microwave-responsive sorbents for high-efficiency direct air capture - Wenjing Li; Mingxing Zhou; Xiaoyan Ji; Yunxia Wen; Han Lin; Xiaohua Lu; Xinwei Zhang; Xiwen Zhang; Tuo Ji; Shuandi Hou; Jiahua Zhu (Chemical Engineering Journal, 2026)

Outdoor thermal comfort differences among orthopedic, oncological and chronic-disease patients in cold-region hospital spaces - Ya Tuo; Songtao Cui; Minghui Sun; Weijie Xia; Songjiang Han; Meng Zhen; Ming Zhang; Kai Nan (Building and Environment, 2026)

Integration of transcriptome and proteome reveals molecular response mechanisms of cryodamage in bovine sperm - Chenglei Song; Qiufei Jiang; Chunmao Zhu; An Shi; Guoxiong Nan; Wenjuan Shen; Jiamin Zhou; Zhuo Yang; Zhengjun Tuo; Xiaohong Han; Jinzhong Tao (Animal Reproduction Science, 2026)

Long-term nitrogen addition alters topsoil SOC fractions via contrasting plant- and soil-mediated pathways in restored grasslands - Xiaoshan Zhang; Hossein Ghanizadeh; Qingsong Jia; Hanghang Tuo; Ziming Yin; Xiaorui Ma; Xiaorong Wei; Xinning Han; Yibo Wang; Huihui Tian; Faming Ye; Qing Yang; et al. (Plant and Soil, 2026)

Prospective motion correction with data reacquisition based on fat navigators for T1-weighted brain MRI at 3T - Minqiang Jia; Bingbing Zhao; Tuo Yu; Jiayu Zhu; Xijing Zhang; Haohao Peng; Xin Ye; Yichen Zhou; Rongrong Xie; Xinju Zhang; Han Zhang; Xiaopeng Zong (Medical & Biological Engineering & Computing, 2026)

Divergent ecohydrological adaptation mechanisms of restored vegetation driven by micro-topography: Structural decoupling, hydro-thermal trade-offs, and competitive depletion - Shaoan Gan; Fengwei Tuo; Lei Han; Yuxuan Ren; Zhao Liu; Hongliang Kang; Jie Liu; Guiming Hu (Ecological Engineering, 2026)

Assessing the Development Potential of Drip Irrigation in Oasis Regions Under Water and Land Constraints: Evidence From the Kashgar Irrigation District - Xiaokaitijiang Kasmu; Zihan Gao; Siqi Han; Yangguang Liu; Tuo Tin; Yunkai Li; Aimidula Aibaidula (Irrigation and Drainage, 2026)
Agricultural development in oasis regions is constrained by the performance of water‐saving technologies and the limitations of land and water resources. However, the effects of land and water constraints on agricultural development potential have rarely been quantified. This study proposes an assessment framework that integrates water‐saving potential under fixed cropland area and cropland expansion potential under limited water availability. Using the Kashgar Irrigation District in Xinjiang as a case study, we quantify the sustainable development space of the agricultural system under coupled land–water constraints through integrated model simulations. The results show that optimizing irrigation, strengthening groundwater regulation and improving efficiency can reduce irrigation water use by 7%–42% and total water consumption by 7%–22%. At the district scale, the drip irrigation scenario yields annual water savings of 4.47 × 10 8 m 3 , equivalent to 30% of the current irrigation demand, representing the primary adjustable margin under fixed land conditions. Without increasing total water withdrawals, these savings could support the expansion of up to 1.09 × 10 5 ha of cropland (approximately 31% of the existing irrigated area). These findings provide transferable insights into irrigation regime optimization and resource reallocation strategies for other oasis regions facing coupled water and land constraints.

Long-term enclosure alters the impact of nitrogen enrichment on the grassland stability of plant productivity, composition and richness - Hanghang Tuo; Hossein Ghanizadeh; Ziming Yin; Xiaorui Ma; Xiaorong Wei; Weijun Li; Xinning Han; Xiaoshan Zhang; Yibo Wang; Huihui Tian; Faming Ye; Qing Yang; et al. (Agriculture, Ecosystems & Environment, 2026)

Post‐Heatwave Coral Health Coincides With Host‐Specific Symbiodiniaceae‐Bacteria Consortia - Han Zhang; Xinqing Zheng; Qifang Wang; Xijie Zhou; Ling Cai; Liyang Zhan; Dingyong Huang; Tuo Shi (Environmental Microbiology, 2026)
Coral reefs are facing unprecedented damage due to climate‐driven marine heatwaves (MHWs). While coral response to elevated temperatures is inextricably linked to coral‐associated microalgae (Symbiodiniaceae) and bacteria, the role of algal‐bacterial interactions in affecting coral resilience to thermal stress remains obscure. Here we show coral health indicated by distinct compositions of Symbiodiniaceae‐bacteria consortia in two coral species, the massive Porites lutea and the laminar Duncanopsammia peltata , upon exposure to an unusual MHW. P. lutea exhibited thermal resilience by maintaining an obligate partnership with the heat‐tolerant Cladocopium C15 under both healthy and bleached states, alongside conservative bacterial community changes between the two states driven primarily by deterministic processes; whereas D. peltata associated with the heat‐sensitive Cladocopium C1 in bleached state but the heat‐tolerant Durusdinium D1/D4 in healthy state, with stochastically driven, more liberal bacterial community changes between the two states. This distinction between P. lutea and D. peltata in their Symbiodiniaceae‐bacteria consortia reflects a specialist/generalist strategy in partner selection given the status of coral health, underscoring an evolutionary trade‐off between high‐fidelity symbioses for persistence under chronic stress and rapid microbiome turnover for transient bleaching resilience. Broadly, the host‐specific, coordinated Symbiodiniaceae‐bacteria community differentiation following MHWs, may inform future coral conservation and restoration practises in an era of escalating climate change.

Breaking the activity-stability trade-off in ammonia borane hydrolysis via atomically engineered platinum single atom-nickel cluster synergistic interfaces - Jiankang Zhang; Panzhe Qiao; Jinlong Hu; Xiuxiu Han; Dan Feng; Hao Xu; Xinshuo Zhao; Jun Zhong; Yongxiao Tuo; Yong Qin; Chaohe Xu (Science Bulletin, 2026)

Divergent responses of soil organic and inorganic carbon to edaphic factors within shelterbelts and croplands in dryland, Northwest China - Tengfei Yu; Tuo Han; Yidan Yin; Baofeng Li; Haiyang Xi; Wei Liu; Qi Feng (Plant and Soil, 2026)

Mitochondrial function meets oncology: the multifaceted role of TFAM across cancer types - Jie Wang; Ruicheng Wu; Fanglin Shao; Zhouting Tuo; Xinrui Li; Koo Han Yoo; Wuran Wei; Zhipeng Wang; Dengxiong Li; Dechao Feng (Apoptosis, 2026)
Mitochondrial transcription factor A (TFAM) is indispensable for mitochondrial DNA (mtDNA) maintenance and transcription, governing cellular bioenergetics. Despite its known physiological importance, TFAM plays a complex and often paradoxical role in cancer biology. This study integrates pan-cancer bioinformatics analyses with experimental evidence to comprehensively elucidate TFAM’s multifaceted impact on tumorigenesis. We systematically investigated the heterogeneity of TFAM across diverse cancer types, specifically focusing on its regulatory mechanisms in metabolic reprogramming, signal transduction, and immune microenvironment remodeling. Our analysis reveals that TFAM functions as a critical node connecting mitochondrial integrity to tumor progression, balancing tumor-promoting and tumor-suppressive roles depending on the context. Finally, we discuss the challenges of targeting TFAM, such as off-target toxicity, and highlight emerging precision oncology strategies, including mitochondria-targeted delivery systems, that aim to exploit these mitochondrial vulnerabilities. Graphical abstract

Soil organic carbon mineralization drives pedogenic inorganic carbon formation in arid riparian forest, Northwest China - Yidan Yin; Tengfei Yu; Tuo Han; Wei Liu; Qi Feng (Applied Soil Ecology, 2026)

Unraveling the role of CaO and MgO as supports in the vanadium-based nitrogen carrier for chemical looping ammonia production - Ziheng Han; Tuo Guo; Yuhai Liu; Yuzhe Lu; Jingjing Ma; Xiude Hu; Qingjie Guo (Chemical Engineering Journal, 2025)

Improved assessment of water-saving effects by global virtual water flow in agri-food trade network with an integrated approach - Yanling Long; Xiuzhi Chen; Yuqian Zhang; Tuo Yin; Siqi Han; Yunkai Li (Journal of Hydrology, 2025)

Wearable radiation monitoring: exploration of A2BX6 perovskite detector screening based on machine learning and DFT - Yali Tuo; Yuxi Du; Changcheng Chen; Yaxin Xu; Zhengjun Wang; Zhao Han; Xiongfei Yun; Jiangzhou Xie; Shuli Gao; Wen Chen; Xiaoning Guan; Gang Liu; et al. (Chemical Engineering Journal, 2025)

Unlocking the synergistic effects in biomass-plastic Co-pyrolysis using a hybrid machine learning approach with blended rule descriptors - Peng Jiang; Wenjie She; Hao Zhang; Lin Li; Han Lin; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Biomass and Bioenergy, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Biomarkers Related to Interferon-γ Pathway in Myocardial Ischemia–Reperfusion Injury and the Potential Molecular Mechanisms - Fang Jia; Wei Jiang; Yan Zhang; Lisha Zhang; Tuo Han; Danmeng Liu; Jiahong Xue; Fuxue Deng (Cardiovascular Toxicology, 2025)

Understanding the microbial processes on carbon brushes that accelerate methanogenesis of long-chain fatty acids in anaerobic digestion - Mou Zhang; Yilian Han; Yuanyuan Zeng; Tuo Wang; Ziyuan Wang; Yuhang Wu; Nan Li; Fernanda Leite Lobo; Xin Wang (Water Research, 2025)

Oxygen-driven metabolic mechanism of feammox process in anaerobic environments - Tuo Wang; Enli Jiang; Yilian Han; Mou Zhang; Yue Sun; Nan Li; Xinlei Jiang; Xin Wang (Chemical Engineering Journal, 2025)

Gyral peak variations between HCP and CHCP: functional and structural implications - Guannan Cao; Songyao Zhang; Zhibin He; Zifan Wang; Lei Guo; Zhiqiang Yan; Junwei Han; Xi Jiang; Tuo Zhang (Brain Structure and Function, 2025)

Highly active vanadium-based nitrogen carrier doped with transition metals during chemical looping ammonia synthesis - Ziheng Han; Xiude Hu; Qiuyan Xue; Tuo Guo; Jingjing Ma; Qingjie Guo (Journal of Cleaner Production, 2025)

Engineering noble metal-free nickel catalysts for highly efficient liquid fuel production from waste polyolefins under mild conditions - Xinlei Han; Jiuxuan Zhang; Zhengyan Qu; Tuo Ji; Feng Zeng; Hong Jiang; Jun Huang; Zhenchen Tang; Weihong Xing; Rizhi Chen (Fuel, 2025)

Construction of diffusion and binding synergy in carbon-supported catalysts with varied Pd0/PdO Ratios for direct synthesis of hydrogen peroxide - Zhiheng Wang; Jiali Huang; Guancong Jiang; Tuo Ji; Han Lin; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Chemical Engineering Journal, 2025)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Networking SiO2-Al2O3 and amines into robust and long-lasting molded sorbents for continuous CO2 capture - Tong Zhou; Zhinan Wu; Yunxia Wen; Zhengxing Dai; Shuailong Song; Han Lin; Xin Feng; Xiaohua Lu; Tuo Ji; Jiahua Zhu (Chemical Engineering Journal, 2024)

Divergent response of upper layer soil organic and inorganic carbon to biotic and abiotic factors in afforestation by aerial seeding in desert, China - Tengfei Yu; Qi Feng; Yidan Yin; Tuo Han; Weiyu Chen; Meng Zhu; Chenguang Zhao; Jing Zhao (CATENA, 2024)

Anode potential regulates gas composition and microbiome in anaerobic electrochemical digestion - Mou Zhang; Tuo Wang; Yilian Han; Xuejun Yan; Xuemei Zhu; Yue Sun; Xinlei Jiang; Xin Wang (Bioresource Technology, 2024)

Seasonally Changing Interactions of Species Traits of Termites and Trees Promote Complementarity in Coarse Wood Decomposition - Chao Guo; Bin Tuo; Sebastian Seibold; Hang Ci; Bi‐Le Sai; Han‐Tang Qin; En‐Rong Yan; Johannes H. C. Cornelissen (Ecology Letters, 2024)
Complementary resource use by functionally different species may accelerate ecosystem processes. However, how co‐variation in plant traits and animal traits promotes complementarity through temporal plant–animal interactions is poorly understood, even less so in detrital systems, thereby hampering our fundamental understanding of decomposition and carbon turnover. We hypothesised that, in seasonal subtropical forests where termites are major deadwood decomposers, trait complementarity of both termite species and tree species should promote overall deadwood decomposition through different seasons and years. Findings from a four‐year coarse wood decomposition experiment involving 27 tree and 5 termite species support this hypothesis. Phenological and mandibular traits of the two most abundant termite species controlled wood decomposition of tree species differing in wood traits, through the seasons over 4 years, thereby promoting overall deadwood decomposition rates. Our findings indicate that complementarity in functional trait co‐variation in plants and animals plays an important role in carbon cycling.

Infection of PRRSV inhibits CSFV C-strain replication by inducing macrophages polarization to M1 - Tianbei Tuo; Dengjin Chen; Lihong Wang; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2024)

Effect of ambient high-temperature on real driving emission tests of a light-duty gasoline vehicle - Rui Wang; Li Zhang; Jingde Peng; Jinlin Han; Baocheng Du; Baoli Gong; Haoyang Xue; Dajiang Tuo; Qing Zhang (Atmospheric Pollution Research, 2024)

Inoculation of cold-adapted microbial consortium screened from alpine meadows promotes the growth of mixed grasses by changing soil properties and enzyme activity - Jiali Chai; Xian Wang; Xiaoting Liu; Changning Li; Jiangru Han; Tuo Yao (Rhizosphere, 2023)

SIRT1 reduction contributes to doxorubicin–induced oxidative stress and meiotic failure in mouse oocytes - Jun Han; Shuo Wang; Huarong Wang; Tuo Zhang; Ye Yang; Ting Zhao; Ziqi Chen; Guoliang Xia; Chao Wang (Toxicology and Applied Pharmacology, 2023)

Divergent response to abiotic factor determines the decoupling of water and carbon fluxes over an artificial C4 shrub in desert - Tengfei Yu; Tuo Han; Qi Feng; Weiyu Chen; Chenguang Zhao; Huiying Li; Junliang Liu (Journal of Environmental Management, 2023)

Synchronous masting regulates seed-seed interactions for two co-fruiting tree species under the mediation of rodents - Jing Wang; Bo Zhang; Ning Han; Tuo Feng; Xiang Hou; Jidong Zhao; Xiaolei An; Xiaoning Chen; Gang Chang (Forest Ecology and Management, 2023)

Grazing practices affect soil microbial networks but not diversity and composition in alpine meadows of northeastern Qinghai-Tibetan plateau - Xiaofang Zhang; Qi Feng; Jianjun Cao; Wei Liu; Yanyan Qin; Meng Zhu; Tuo Han (Environmental Research, 2023)

PRRSV inhibited the proliferation of CSFV by inducing IL-1β maturation via NLRP3 inflammasome activation - Dengjin Chen; Tianbei Tuo; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2023)

Effects of afforestation by aerial sowing on topsoil physicochemical properties in the sandy desert, NW China - Weiyu Chen; Tengfei Yu; Tuo Han; Chenguang Zhao; Huiying Li; Xuejuan Liu; Junliang Liu; Xiaoyou Zhang (Journal of Soils and Sediments, 2023)

Resveratrol-induced SIRT1 activation inhibits glycolysis-fueled angiogenesis under rheumatoid arthritis conditions independent of HIF-1α - Tian-Tian Jiang; Cong-Lan Ji; Li-Jun Yu; Meng-Ke Song; Yan Li; Qiang Liao; Tuo Wei; Opeyemi Joshua Olatunji; Jian Zuo; Jun Han (Inflammation Research, 2023)

Crop types and irrigation regimes as drivers of plastisphere bacterial communities in plastic-mulching croplands of subtropical China - Gongwen Luo; Qirui Zhu; Tuo Jin; Jianwei Peng; Ning Zuo; Huiru Zhang; Mengjiao Geng; Ying Huang; Yongliang Han; Chang Tian; Yong Yang; Jiangchi Fei (Applied Soil Ecology, 2023)

Intracellular kynurenine promotes acetaldehyde accumulation, further inducing the apoptosis in soil beneficial fungi Trichoderma guizhouense NJAU4742 under acid stress - Han Zhu; Tuo Li; Chi Li; Yang Liu; Youzhi Miao; Dongyang Liu; Qirong Shen (Environmental Microbiology, 2023)
In this study, the growth of fungi Trichoderma guizhouense NJAU4742 was significantly inhibited under acid stress, and the genes related to acid stress were identified based on transcriptome analysis. Four genes including tna 1, adh 2/4, and bna 3 were significantly up‐regulated. Meanwhile, intracellular hydrogen ions accumulated under acid stress, and ATP synthesis was induced to transport hydrogen ions to maintain hydrogen ion balance. The enhancement of glycolysis pathway was also detected, and a large amount of pyruvic acid from glycolysis was accumulated due to the activity limitation of PDH enzymes. Finally, acetaldehyde accumulated, resulting in the induction of adh 2/4. In order to cope with stress caused by acetaldehyde, cells enhanced the synthesis of NAD + by increasing the expression of tna 1 and bna 3 genes. NAD + effectively improved the antioxidant capacity of cells, but the NAD + supplement pathway mediated by bna 3 could also cause the accumulation of kynurenine (KYN), which was an inducer of apoptosis. In addition, KYN had a specific promoting effect on acetaldehyde synthesis by improving the expression of eno 2 gene, which led to the extremely high intracellular acetaldehyde in the cell under acidic stress. Our findings provided a route to better understand the response of filamentous fungi under acid stress.

Chestnut caching behavior of Chinese white-bellied rats (Niviventer confucianus) and South China field mice (Apodemus draco): effects of seed size and insect infestation - Xiao-Lei An; Bo Zhang; Tuo Feng; Ning Han; Jing Wang; Xiao-Ning Chen; Ji-Dong Zhao; Ming Qin; Gang Chang; Xiang Hou (Behavioral Ecology and Sociobiology, 2022)

Cortical development coupling between surface area and sulcal depth on macaque brains - Xiao Li; Songyao Zhang; Xi Jiang; Shu Zhang; Junwei Han; Lei Guo; Tuo Zhang (Brain Structure and Function, 2022)

Probiotic and Safety Properties Screening of Enterococcus faecalis from Healthy Chinese Infants - Juan Wang; Rong Da; Xiaohong Tuo; Yue Cheng; Jie Wei; Kaichong Jiang; Jia Lv; Omolade Monisayo Adediji; Bei Han (Probiotics and Antimicrobial Proteins, 2020)

Decadal change in summer precipitation over the east of Northwest China and its associations with atmospheric circulations and sea surface temperatures - Shasha Shang; Gaofeng Zhu; Ruolin Li; Jie Xu; Juan Gu; Huiling Chen; Xiaowen Liu; Tuo Han (International Journal of Climatology, 2020)
As global warming has progressed, precipitation patterns over arid Northwest China have undergone significant change. In this study, changes in summer (JJA) precipitation over the eastern part of Northwest China (ENWC) from 1980 to 2014 were investigated using the China gridded monthly precipitation dataset (CN05.1). The results showed that summer precipitation over the ENWC experienced a decadal wet‐to‐dry shift in 1998. Westerlies played an important role in the upper atmospheric levels in terms of water vapour transport; the decadal variations in summer precipitation were principally controlled by the water vapour input from the ENWC's western boundary. In addition, the decadal variations in summer precipitation in the ENWC appear to be associated with a meridional teleconnection around 110°E and a zonal pattern over 45–60°N in the lower troposphere. These two teleconnections led to cyclonic anomalies in the ENWC and enhanced water vapour transport into the ENWC, resulting in above‐normal precipitation during the 1989–1998 decadal period. Further, the warmer (colder) sea surface temperatures (SSTs) observed in the tropical Eastern Pacific correspond to the southward (northward) displacement of the Asian jet stream and a negative (positive) phase of the Silk Road pattern, resulting in a wet (dry) ENWC. Moreover, the SST anomalies in the North Atlantic and Northwest Pacific may affect summer precipitation over the ENWC via a zonal teleconnection in the middle troposphere.

Community structure and function of cultivable Endophytic Bacteria isolated from four Moss species in Qilian Mountain - Xiaojun Lan; Heng Zhou; Tuo Yao; Wanqing Dong; Jiangui Zhang; Dongrong Han (Symbiosis, 2020)

Soil respiration in an irrigated oasis agroecosystem: linking environmental controls with plant activities on hourly, daily and monthly timescales - Ting Ma; Gaofeng Zhu; Jinzhu Ma; Kun Zhang; Shangtao Wang; Tuo Han; Shasha Shang (Plant and Soil, 2020)

Sensitivity analysis and estimation using a hierarchical Bayesian method for the parameters of the FvCB biochemical photosynthetic model - Tuo Han; Gaofeng Zhu; Jinzhu Ma; Shangtao Wang; Kun Zhang; Xiaowen Liu; Ting Ma; Shasha Shang; Chunlin Huang (Photosynthesis Research, 2020)

Extendable supervised dictionary learning for exploring diverse and concurrent brain activities in task-based fMRI - Shijie Zhao; Junwei Han; Xintao Hu; Xi Jiang; Jinglei Lv; Tuo Zhang; Shu Zhang; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2018)

Basidiomycete‐specific PsCaMKL1 encoding a CaMK‐like protein kinase is required for full virulence of Puccinia striiformis f. sp. tritici - Min Jiao; Dan Yu; Chenglong Tan; Jia Guo; Dingyun Lan; Ershang Han; Tuo Qi; Ralf Thomas Voegele; Zhensheng Kang; Jun Guo (Environmental Microbiology, 2017)
Summary Calcium/calmodulin‐dependent kinases (CaMKs) are Ser/Thr protein kinases (PKs) that respond to changes in cytosolic free Ca 2+ and play diverse roles in eukaryotes. In fungi, CAMKs are generally classified into four families CAMK1, CAMKL, RAD53 and CAMK‐Unique. Among these, CAMKL constitutes the largest family. In some fungal plant pathogens, members of the CaMKL family have been shown to be responsible for pathogenesis. However, little is known about their role(s) in rust fungi. In this study, we functionally characterized a novel PK gene, PsCaMKL1 , from Puccinia striiformis f. sp. tritici ( Pst ). Ps CaMKL1 belongs to a group of PKs that is evolutionarily specific to basidiomyceteous fungi. Ps CaMKL1 shows little intra‐species polymorphism between Pst isolates. PsCaMKL1 transcripts are highly elevated at early infection stages, whereas gene expression is downregulated in barely germinated urediospores under KN93 treatment. Overexpression of PsCaMKL1 in fission yeast increased resistance to environmental stresses. Knock down of PsCaMKL1 using host‐induced gene silencing (HIGS) reduced the virulence of Pst accompanied by reactive oxygen species (ROS) accumulation and a hypersensitive response. These results suggest that Ps CaMKL1 is a novel pathogenicity factor that exerts it virulence function by regulating ROS production in wheat.

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

Commonly preserved and species-specific gyral folding patterns across primate brains - Xiao Li; Hanbo Chen; Tuo Zhang; Xiang Yu; Xi Jiang; Kaiming Li; Longchuan Li; Mir Jalil Razavi; Xianqiao Wang; Xintao Hu; Junwei Han; Lei Guo; et al. (Brain Structure and Function, 2017)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Identifying and Characterizing Resting State Networks in Temporally Dynamic Functional Connectomes - Xin Zhang; Xiang Li; Changfeng Jin; Hanbo Chen; Kaiming Li; Dajiang Zhu; Xi Jiang; Tuo Zhang; Jinglei Lv; Xintao Hu; Junwei Han; Qun Zhao; et al. (Brain Topography, 2014)

Group-Wise FMRI Activation Detection on DICCCOL Landmarks - Jinglei Lv; Lei Guo; Dajiang Zhu; Tuo Zhang; Xintao Hu; Junwei Han; Tianming Liu (Neuroinformatics, 2014)

Resting State fMRI-guided Fiber Clustering: Methods and Applications - Bao Ge; Lei Guo; Tuo Zhang; Xintao Hu; Junwei Han; Tianming Liu (Neuroinformatics, 2013)

Meta-Analysis of Functional Roles of DICCCOLs - Yixuan Yuan; Xi Jiang; Dajiang Zhu; Hanbo Chen; Kaiming Li; Peili Lv; Xiang Yu; Xiaojin Li; Shu Zhang; Tuo Zhang; Xintao Hu; Junwei Han; et al. (Neuroinformatics, 2013)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

In vitro assessment of immunomodulating activity of the two Lactobacillus strains isolated from traditional fermented milk - Yanfeng Tuo; Lanwei Zhang; Xue Han; Ming Du; Yingchun Zhang; Huaxi Yi; Weiqin Zhang; Yuehua Jiao (World Journal of Microbiology and Biotechnology, 2011)

Three-dimensional conjugate gradient inversion of magnetotelluric full information data - Chang-Hong Lin; Han-Dong Tan; Tuo Tong (Applied Geophysics, 2011)